2009
DOI: 10.1007/s00535-009-0088-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary olive oil prevents carbon tetrachloride-induced hepatic fibrosis in mice

Abstract: Dietary olive oil prevents CCl(4)-induced tissue injury and fibrosis in the liver. Since oleic acid inhibited activation of HSCs, oleic acid may play a key role on this mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…This result agrees with that of Wu et al [42] and Tanaka et al [43] who reported decreased food intake due to toxicity with CCl 4 . Moreover, decrease in food intake was detected after administration of olive oil and Nigella sativa to rats received CCl 4 .…”
Section: Discussionsupporting
confidence: 93%
“…This result agrees with that of Wu et al [42] and Tanaka et al [43] who reported decreased food intake due to toxicity with CCl 4 . Moreover, decrease in food intake was detected after administration of olive oil and Nigella sativa to rats received CCl 4 .…”
Section: Discussionsupporting
confidence: 93%
“…In line, retinoid or retinoic acid have been shown to attenuate liver fibrogenesis in cultured HSC and in vivo in CCl 4 ‐induced liver injury through the inhibitory effects of collagen type I production and reduced liver injury from oxidative stress (34, 35). In addition, recent reports confirm that oleic acid reduce the severity of CCl 4 ‐induced liver fibrosis (36, 37). LCN2, therefore, might be relevant in fibrogenesis with regard to retinol transport, reception and storage in HSC.…”
Section: Resultsmentioning
confidence: 91%
“…Indeed, while oleic acid can be synthesized de novo through the activity of the Stearoyl-CoA desaturase 1 (SCD1), it is clear from results obtained in germline Scd1 KO mice [47], liver-specific Scd1 KO mice [8;9] and in mice overexpressing Scd3 [10] that oleate can contribute to various physiological functions, notably in liver. Dietary olive oil [11] and oleic acid [12] have been shown to have beneficial effects in different experimental models of hepatic pathologies termed Non Alcoholic Fatty Liver Diseases (NAFLD) that range from steatosis to steatohepatitis (NASH). Despite its promoting effect on hepatic lipid accumulation, oleic acid synthesized de novo also contributes to protect hepatocytes from insulin resistance [13].…”
Section: Introductionmentioning
confidence: 99%